A minimal change disease (MCD) related nephrotic syndrome preceding a Hodgkin Lymphoma diagnosis - A case report - Castro,Pedro Almiro e (2022)
ABSTRACT We admitted a 21‑year‑old female to the Nephrology ward due to proteinuria and generalized oedema, which started soon after consuming clonixin 300mg thrice a day for two weeks. Her initial blood work showed nephrotic‑range proteinuria, hypoalbuminaemia, hypercholesterolaemia and normal kidney function. We conducted a full auto‑immune and serological study: there were no signs of infection, complemente consumption or underlying auto‑immune diseases. Suspecting minimal change disease, we started prednisolone 1mg/kg/day, with good clinical response and a reduction of urinary protein losses. By the third day, a kidney biopsy was performed: the glomeruli were morphologically normal and no immune deposits were found, which suggested minimal change disease. After seven days, the patient was discharged from the hospital with a corticoid taper until her Nephrology consultation. In the following weeks she maintained clinical and laboratorial remission and prednisolone was stopped after six months. Two months after, the patient noticed a growing bilateral cervical mass and went to the emergency room. The diagnostic workup was inconclusive, so an ultrasound‑guided biopsy was requested. The biopsy revealed lymphoid cell proliferation, positive for CD30, CD15, MUM‑1 and BCl6. These findings confirmed a Hodgkin’s Lymphoma diagnosis and the patient started radiotherapy and chemotherapy (ABVD‑doxorubicin, bleomycin, vinblastin, dacarbazine). In the following months her clinical status improved and the cervical mass had a significant size reduction. The kidney disease remained in remission, without therapeutic adjustments. A post‑treatment PET scan was requested, showing only a residual mediastinal mass.